The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/ors.12022
|View full text |Cite
|
Sign up to set email alerts
|

A service review of a novel primary care specialist oral surgery referral service operating in a managed clinical network

Abstract: Aim: This paper describes a newly created primary care oral surgery specialist service operating in a managed clinical network caring for the United Kingdom military population. It aims to review its outcomes and to consider the structure of the service in relation to the recommendations of the 2010 NHS sponsored 'Review of Oral Surgery Services and Training' by Medical Education England which made recommendations for the delivery of UK oral surgery services. Materials and methods: A retrospective audit of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
2
7
0
Order By: Relevance
“…Over the last few years, primary care trusts in England have established referral pathways for treatment by oral surgeons in primary care. The findings of our study are consistent with the studies reported in this literature …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Over the last few years, primary care trusts in England have established referral pathways for treatment by oral surgeons in primary care. The findings of our study are consistent with the studies reported in this literature …”
Section: Discussionsupporting
confidence: 93%
“…One patient had persistent pain post‐extraction who was referred to oral and maxillofacial surgery unit locally and diagnosed as osteomyelitis. Overall complications were consistent with a standard practice of oral surgery.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…2018;7(3): [30][31][32][33][34][35][36][37] Existing UK data from oral surgery services based in primary care report acceptable referral systems, better accessibility, shorter waiting times and lower costs than those provided in hospital services, yet with comparable outcomes. [8][9][10][11][12][13] However, with few exceptions, previous evaluations have been narrow in focus and assessed certain aspects of the quality of care and undertaken before the publication of recent commissioning guidance. 4 Service evaluations can take a range of forms, 14 but they broadly assess whether the aims of a service are being met and analyse the reasons for any discrepancies.…”
Section: Thomas Anthony Dyer Jessica Ga Lai Laumentioning
confidence: 99%